Aspek Ritual pada Sistem Irigasi Subak sebagai Warisan Budaya Dunia - Wayan Windia; Sumiyati; Gede Sedana (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
This paper introduces some ritual activities performed byindividual farmer within subak system. Subak is farmersmanaged irrigation system which has an irrigation watersource irrigated to certain compound of rice fields and hasa particular temple. The ritual ceremony is a part of importantthing of Tri Hita Karana (THK) implementation, namelyparhyangan aspect presenting the harmonious relationshipbetween farmer and the God. The other components of THKare pawongan (the harmonious relationship among subak’smembers) through the implementation of subak’s regulation(awig-awig); and palemahan presenting the harmoniousrelationship between farmer and environment through therice field terrace maintenance. There are 16 activities of ritualceremonies individually performed by farmer as subak’smember starting from the ritual of fetching irrigation wateruntil the post-harvest ritual ceremony. Aside from this, thereare also ritual ceremonies conducted by the all members atthe subak level. Subak also has ritual ceremonies carried outtogether with the other subaks in the temples located near thedam, lake and others. These ritual activities constitute as acultural practices conducted by subak. Therefore, subak hasbeen regarded as the keeper of Balinese culture by implementingTHK, thus UNESCO has acknowledged subak asworld cultural heritage.